2009
DOI: 10.1007/s00436-009-1355-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dequalinium on the oxidative stress in Plasmodium berghei-infected erythrocytes

Abstract: The bisquinoline drug dequalinium (DQ) has demonstrated remarkable activity against some infection diseases, including malaria. Oxidative stress represents a biochemical target for potential antimalarials. In this work, we have tested the ability of this compound to modify the oxidative status in Plasmodium berghei-infected erythrocytes. After hemolysis, activities of superoxide dismutase (SOD), catalase (CAT), glutathione cycle, and dehydrogenase enzymes were investigated. The activity of glucose-6-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
6
7
0
Order By: Relevance
“…In fact, it has been documented that in Plasmodium infection excessive production of free radicals or oxidants is possible and may impair antioxidant system. (Rodrigues and Gamboa 2009). Therefore, the observed elevation in MDA values of infected mice in this study is in concordance with those findings (Farombi et al 2003;Rodrigues and Gamboa 2009).…”
Section: Discussionsupporting
confidence: 82%
“…In fact, it has been documented that in Plasmodium infection excessive production of free radicals or oxidants is possible and may impair antioxidant system. (Rodrigues and Gamboa 2009). Therefore, the observed elevation in MDA values of infected mice in this study is in concordance with those findings (Farombi et al 2003;Rodrigues and Gamboa 2009).…”
Section: Discussionsupporting
confidence: 82%
“…This effect could be beneficial, protecting the cells from haemolysis, which results in the development of the anaemia typically observed in malaria patients. This is in agreement with data published on another cycloalcanone, which did not cause lipid peroxidation in erythrocytes (Palmen & Evelo 1998) as well as data on another quinoline derivative, which also diminished malondialdehyde levels in infected cells (Rodrigues & Gamboa 2009). Nevertheless, this result is contradictory because both quinoline compounds seem to promote oxidative stress in infected cells.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that SOD activity decreased markedly during infection, which is in agreement with results demonstrated in malaria patients and in P. berghei-infected erythrocytes (Farombi et al 2003, Rodrigues & Gamboa 2009); however, treatment with IQ and CQ prevented some loss of the activity of this enzyme compared to infected, untreated cells. This event could be produced in response to a compensatory effect due to modification of the glutathione cycle and hexose-monophosphate activity, results that were also reported for the bis-quinoline compound dequalinium (Rodrigues & Gamboa 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This includes pharyngeal sprays, throat lozenges, mouth washes and decongestant sprays, topical creams, gels, and ointments, as well as tablets or suppositories for vaginal application. Beside its antibacterial activity, dequalinium has been reported to exhibit an array of other biological effects such as potent antitumor activity through toxicity against mitochondria, [8][9][10][11][12] inhibition of protein kinase C, [13,14] antimalarial, [15][16][17] antitrypanosomal, [3,6] and antifungal [7] activities, inhibition of mycothiol ligase in Mycobacterium tuberculosis, [5] selective blockade of small-conductance Ca 2 + -activated K + channels, [18][19][20][21][22][23][24] and disintegration of amyloid fibrils. [25] In addition to these effects, dequalinium's toxicity has also been reported; it may cause skin necrosis if administered on intertriginous skin areas under occlusive conditions.…”
Section: Dequaliniummentioning
confidence: 99%